Eden - Sebela, Christopher; Bismut, Alain; Ferry, Abel, 1973- (Humanoids, Inc., 2024)
"The world is dying. As government and the environment crumble, humanity's only hope is Eden, a newly discovered Earth-like planet unspoiled by the folly of man. Massive Edencorp spaceships begin to shuttle millions of people lucky enough to be chosen by the lottery to the bright future of Eden... but a bright future for whom?" --